Emisi Karbon dan Produk Domestik Bruto: Investigasi Hipotesis Environmental Kuznets Curve (EKC) pada Negara Berpendapatan Menengah di Kawasan ASEAN - Muhamad Ameer Noor; Putu Mahardika Adi Saputra (Jurnal Wilayah dan Lingkungan, 2020)
Policymakers in the world are concerned with carbon emission due to the risk of global warming. Many studies on Environmental Kuznets Curve (EKC) consider carbon emission as a proxy of environmental degradation. This study aimed to investigate the existence of EKC and identify variations of relationships between carbon emissions and GDP per capita in ASEAN middle-income countries. The study was conducted on Indonesia, Thailand, Philippines, and Malaysia based on 1971-2014 time series data using a simultaneous model (2SLS) for each country. The main variables studied were GDP per capita, square of GDP per capita, and carbon emission supported by other variables as the controlling variables. Validation on EKC existence was determined by GDP and GDP squared influence on carbon emission, while variations of relationship between GDP and carbon emission were based on the result of simultaneous regressions. The results showed that the existence of the EKC could not be validated in all countries because energy and transportation policies in each country failed to reduce the emission. On the other hand, carbon emission had a positive unidirectional influence on GDP in all countries. The effect of carbon emission coefficient to GDP showed that Thailand ranked the highest in CO2 efficiency, followed by Indonesia, Philippines, and Malaysia. This study recommended that carbon emission reduction policies in the four countries should focus more to easier access to environmentally friendly technology from developed countries for ensuring trade-offs between the economy and environment.